Study Analysis on the High-Level Viaduct Over Bondivagu Drain - Haripriya, Sandela; Venkat Reddy, P; Laxmi Prasanna, E (International Journal of Engineering and Technology, 2018)
A viaduct is a structure used to hold obstacles such as water, road, valley. It also provides the way for these obstacles. Assorted designs of proposals serve various purposes and can be applied for different situations. Depending up on the usage of bridge its function will be varied and the factors that comes into action are nature, location of the proposal, materials used for its framework also amount that is authorized to construction.In this paper we are presenting the study analysis on the high-level viaduct over Bondivagu drain. Construction of high-level viaduct over Bondivagu drain. As it approaches way of Hanamkonda to Warangal. The distance from Hanamkonda to Warangal is 4km approximately and this drain Bondivagu is located in a span of 2.5km from Hanamkonda and 1.5km from Warangal.Through this bridge the bypass road of Hanamkonda to Khammam passes.Â Â